A 45° tilted 3D-printed scanner for compact side-view laser scanning endoscopy - Savas, Janset; Altinsoy, Melisa; Gokdel, Yigit Daghan; Ferhanoglu, Onur; Civitci, Fehmi (Springer Heidelberg, 2020)
Side viewing, miniaturized laser scanning endoscopes are powerful tools in providing sub-cellular level resolution and multi-layered imaging of the walls of body cavities. Yet, the level of miniaturization for such devices is significantly hampered by the necessity for 45 degrees placement of the whole scanner unit with respect to the cavity axis. With its rapid and low-cost production capability, 3D printing can be employed in addressing the challenge of producing a laser scanner, whose scanning head makes 45 degrees, or any desired angle, with the scanner unit. Producing a 10 x 10 mm(2) scanner device with tilted scan head (as opposed to the conventional design with identical size) enabled size shrinkage of a near fully 3D-printed laser scanning imager by x 1.5 in diameter (from 17 to 11 mm). We also share the initial results on 5 x 5 mm(2) total die size scanners, having literally identical die size with their MEMS counterparts, and discuss the road steps in producing < 8-mm diameter laser scanning devices with these scanners using 3D printing technology. The frame-rate improvement strategies are discussed in detail. Furthermore overall resolution and frame-rate values that can be achieved with the presented 3D printed scanners are tabulated and compared to MEMS counterparts. Overall with their low cost, easy and rapid fabrication, 3D printed actuators are great candidates for opto-medical imaging applications.